2021
DOI: 10.3390/mi12111307
|View full text |Cite
|
Sign up to set email alerts
|

Using High-Power UV-LED to Accelerate a Decatungstate-Anion-Catalyzed Reaction: A Model Study for the Quick Oxidation of Benzyl Alcohol to Benzoic Acid Using Molecular Oxygen

Abstract: High-power UV-LED irradiation (365 nm) effectively accelerated the decatungstate-anion-catalyzed oxidation of benzyl alcohol 1 to benzoic acid 3 via benzaldehyde 2. As the power of the UV-LED light increased, both the selectivity and yield of benzoic acid also increased. The reaction was finished within 1 h to give 3 in a 93% yield using 2 mol% of decatungstate anion catalyst. The combination of a flow photoreactor and high-power irradiation accelerated the oxidation reaction to an interval of only a few minut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
0
12
0
1
Order By: Relevance
“…Finally, to accelerate the photocatalytic oxidative cleavage reaction, we examined a flow oxidation reaction using a photo flow reactor and a high-power UV LED (365 nm, 240 W), because we learned in our recent work that the oxidation of benzyl alcohol to benzoic acid could be effectively accelerated under flow conditions. , As illustrated in Scheme , an aqueous acetonitrile solution containing 1a (50 mM) and the decatungstate catalyst (2 mol %) was mixed with molecular oxygen using a T-shaped mixer and the gas/liquid mixture was then introduced into a PFA tubing reactor. We found that a high-speed oxidation occurred with acetophenone ( 2a ) being produced in 89% GC yield in a much shorter reaction (residence) time of 6 min compared with the batch protocol.…”
mentioning
confidence: 99%
“…Finally, to accelerate the photocatalytic oxidative cleavage reaction, we examined a flow oxidation reaction using a photo flow reactor and a high-power UV LED (365 nm, 240 W), because we learned in our recent work that the oxidation of benzyl alcohol to benzoic acid could be effectively accelerated under flow conditions. , As illustrated in Scheme , an aqueous acetonitrile solution containing 1a (50 mM) and the decatungstate catalyst (2 mol %) was mixed with molecular oxygen using a T-shaped mixer and the gas/liquid mixture was then introduced into a PFA tubing reactor. We found that a high-speed oxidation occurred with acetophenone ( 2a ) being produced in 89% GC yield in a much shorter reaction (residence) time of 6 min compared with the batch protocol.…”
mentioning
confidence: 99%
“…Yields were determined by using the percentage peak area method with compensation for the relative sensitivities of each component. Product 2 and byproduct 2' were confirmed by 1 H and 13 C NMR analysis (see Supporting Information File 1).…”
Section: Methodsmentioning
confidence: 89%
“…We thought that if rationally designed scalable photoflow setups were available, flow C-H chlorination reactions using chlorine gas would be able to focus on production. In this study, we tested a novel photoflow setup consisting of quartz-made straight-line reactors, which are provided from MiChS (LX-1, Figure 1a) and a high-power LED (MiChS LED-s, 365 ± 5 nm, Figure 1b) [13]. Each channel track has a 2 mm depth and 557 mm length, while the width varies from 6 or 13 mm depending on the number of channels 7 or 5, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Photocatalytic aerobic oxidation of benzyl alcohol has emerged as a green methodology for the synthesis of useful industrial chemical intermediates (e.g., benzaldehyde, benzoic acid). , To evaluate the photocatalytic activities of compounds 1 – 3 , the photocatalytic aerobic oxidation of benzyl alcohol was selected as a model reaction, which was carried out at room temperature under 10 W 365 nm light irradiation. Before the reaction, the influencing factors such as the solvent and the amount of catalyst were screened using compound 1 as a heterogeneous photocatalyst (Table ).…”
Section: Results and Discussionmentioning
confidence: 99%